Facetas do trabalho docente na pandemia: uma escrevivência de professoras alfabetizadoras em Foz do Iguaçu - PR - Baltruk, Soraia Cristina Weidman (2024)
In 2020 and 2021, all municipal schools in Foz do Iguaçu were closed due to the COVID-19 pandemic. This closure required authorities to establish strategies so that the student-school bond was not lost. To this end, the special regime for differentiated remote pedagogical actions, known as ERE – Emergency Remote Education, was implemented in the municipality, which consisted of printed activities and/or mediated by digital communication technologies. This study sought to investigate how literacy teachers from the municipal network of Foz do Iguaçu perceived teaching work in the process of teaching reading and writing remotely. The objective was to record the testimonies, reflect and raise discussions about teaching work during the pandemic period. To this end, a Focus Group was formed with five teachers who acted as regent 1 in first-year classes during the pandemic years. Using the spontaneous conversation technique focused on the topic, literacy permeated the three meetings, but other facets of the teachers' experiences emerged that resulted in the writing of their experiences and the emphasis on five facets of pedagogical work during the pandemic. The analysis is carried out using Content Analysis and the discussion of themes involves the interdisciplinarity of the Sociology of Experience (Dubet, 1994) with studies on literacy by Magda Soares (2020) and Cagliari (2009), on the work of Ricardo Antunes (2018) and Pedagogy of Autonomy by Paulo Freire (2002) among others. The data constructed from the statements allowed us to conclude that teaching work is permeated by various conditions that affect teachers personally and professionally. During the pandemic period, official documents determined pedagogical practices regardless of the reality of each school, undermining the autonomy of teachers as experts in their classes, despite the emotional bond not having been established at the beginning of the year. It also allowed us to conclude that without intentional and qualified mediation it is not possible to teach a first-year child to read and write, and that this depends on his family, in the absence of the teacher. However, the family is not always able to exercise this competent mediation. Another conclusion reached is that, as in other regions of the country, social inequalities were determinants of exclusion from the ERE process, since many families did not have resources for food and equipment such as cell phones, tablets or quality internet. An important point of the research was that the teachers pointed out the physical and emotional exhaustion that working in a home office system generated, since chronological school time disappeared and work invaded their families' personal space. Anxiety and depression were reported to be exacerbated during the pandemic period, due to the exercise of the profession. As a consequence of all these factors, the facet of self-exploration, which together with the facets of literacy, human suffering, regulations and pedagogical work form the whole of teaching work during the pandemic reported here as write experience, which is the report made from within out, teacher with teachers.